Cardiovascular Disease Could Be Contained Based on Currently Available Data! - Okom Nkili F.C. Ofodile (SAGE Publishing, 2006)
Largely due to better control of infectious diseases and significant advances in biomedical research, life expectancy worldwide has increased dramatically in the last three decades. However, as the average age of the population has risen, the incidence of chronic age-related diseases such as arthritis, Alzheimer's, Parkinson's, cardiovascular disease, cancer, osteoporosis, benign prostatic hyperplasia, and late-onset diabetes have increased and have become serious public health problem, as well. The etiology of these disorders is still incompletely understood, therefore, neither preventive strategies nor long-term effective treatment modalities are available for these disorders. In keeping with the aforementioned, the ultimate goal in cardiovascular research is to prevent the onset of cardiovascular episodes and thereby allow successful ageing without morbidity and cognitive decline. Herein, I argue that cardiovascular episodes could be contained with relatively simple approaches. Cardiovascular disorder is characterized by cellular and molecular changes that are commonplace in age-related diseases in other organ system, such alterations include increased level of oxidative stress, perturbed energy metabolism, and "horror autotoxicus" largely brought about by the perturbation of ubiquitin -proteasome system, and excessive oxidative stress damage to the cardiac muscle cells and tissues, and cross-reactions of specific antibodies against human heat shock protein 60 with that of mycobacterial heat shock protein 65." Horror autotoxicus", a Latin expression, is a term coined by Paul Ehrlich at the turn of the last century to describe autoimmunity to self, or the attack of "self" by immune system, which ultimately results to autoimmune condition. Based on the currently available data, the risk of cardiovascular episodes and several other age-related disorders, including cancer, Alzheimer's disease and diabetes, is known to be influenced by the nature and level of food intake. Now, a wealth of scientific data from studies of rodents and monkeys has documented the significant beneficial effects of calorie restriction (CR) or dietary restriction (DR), and multiple antioxidant agents in extending life span and reducing the incidence of progeroid-related diseases. Reduced levels of cellular oxidative stress, protection of genome from deleterious damage, detoxification of toxic molecules, and enhancement of energy homeostasis, contribute to the beneficial effects of dietary restriction and multiple antioxidant agents. Recent findings suggest that employment of DR and multiple antioxidant agents (including, catalase, gluthatione peroxidase, CuZn superoxide dismutase, and Mn superoxide dismutase = enzymes forming the primary defense against oxygen toxicity), and ozone therapy may mount an effective resistance to pathogenic factors relevant to the pathogenesis of cardiovascular episodes. Hence, while further studies will be needed to establish the extent to which CR and multiple antioxidant agents will reduce incidence of cardiovascular episodes in humans, it would seem prudent to recommend CR and multiple antioxidant agents as widely applicable preventive approach for cardiovascular disorders and other progeroid-related disorders.